2014
DOI: 10.1007/s12595-014-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics on Survival, Growth and Digestive Enzymes Activities in Freshwater Prawn Macrobrachium rosenbergii (De Man 1879)

Abstract: A study was conducted to examine the effects of three probiotics, Lactobacillus sporogenes, Bacillus subtilis and Saccharomyces cerevisiae on the survival, growth and digestive enzymes activities of the freshwater prawn Macrobrachium rosenbergii post larvae (PL). The probiotics, L. sporogenes (4 %), B. subtilis (3 %) and S. cerevisiae (4 %) were taken and mixed with basal diet. Diet without probiotics served as control. These probiotics diets were fed to M. rosenbergii PL for a period of 60 days. After the fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…There are several studies demonstrating the positive effects of probiotics Bacillus spp. on the growth of M. rosenbergii (Keysami et al., ; Kumar et al., ; Mujeeb Rahiman, Jesmi, Thomas, & Mohamed Hatha, ; Seenivasan, Radhakrishnan, Muralisankar, & Saravana Bhavan, ). For instance, Kumar et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies demonstrating the positive effects of probiotics Bacillus spp. on the growth of M. rosenbergii (Keysami et al., ; Kumar et al., ; Mujeeb Rahiman, Jesmi, Thomas, & Mohamed Hatha, ; Seenivasan, Radhakrishnan, Muralisankar, & Saravana Bhavan, ). For instance, Kumar et al.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies demonstrating the positive effects of probiotics Bacillus spp. on the growth of M. rosenbergii(Keysami et al, 2012;Kumar et al, 2013;Mujeeb Rahiman, Jesmi, Thomas, & Mohamed Hatha, 2010;Seenivasan, Radhakrishnan, Muralisankar, & Saravana Bhavan, 2016). For instance,Kumar et al (2013) showed that dietary Bacillus licheniformis addition at 1 × 10 9 cfu/g significantly improved the growth performance in M. rosenbergii juveniles after 60 days of feeding.…”
mentioning
confidence: 96%
“…In this context, Zhao et al (2015) proved that shrimp feed in which fish meal was replaced by yeast extract, showed a higher apparent protein digestibility (APD) than control treatment in Penaeus vannamei, stating that approximately 45% of fish meal can be replaced by the yeast extract, in the presence of fish oil, phosphorus and calcium. For M. rosenbergii postlar-vae, Prasad et al (2013) suggest that feeds containing 0.5% S. cerevisiae yeast, are suitable to promote growth, although Seenivasan et al (2014) reported that yeast inclusion levels at 4%, improved growth, enzyme activity, and amino acid production. Similarly, Parmar et al (2012) demonstrated that 1% yeast inclusion in the diet improve the immune response, and control of white muscle disease.…”
Section: Discussionmentioning
confidence: 99%
“…Freshwater prawns and penaeid shrimp have similar proportions of body amino acids (D'Abramo & New ). However, differences in amino acid requirements of decapods are also related to osmoregulatory demand that depends on the marine or freshwater environment (Gu, Friedman, Jost, Johnsson, Kamali‐Moghaddam, Plückthun & Söderberg ; Seenivasan, Radhakrishnan, Muralisankar & Bhavan ).…”
Section: Discussionmentioning
confidence: 99%